EFFECT OF INTRATRACHEAL FIBRES EXPOSURE ON THE RAT LUNG - Kovacikova, Zuzana; Hurbankova, Marta; Tatrai, Erzsebet; Cerna, Silvia (Biomedical papers, 2005)
The changes in antioxidant status of rat lung after intratracheal instillation of stone-wool and glass fibres were studied. The animals were exposed to 2 or 8 mg of fibres for 4 or 16 weeks, the bronchoalveolar lavage was performed and the activity of superoxide dismutase, glutathione peroxidase and the total amount of glutathione was estimated both in tissue and in cell free fraction of bronchoalveolar lavage and the ascorbic acid was determined in lung tissue. The results showed the higher burden by stone-wool. Most changes were detected in groups exposed to higher dose of fibres for shorter time period, the most sensitive parameter was superoxide dismutase. The lung tissue was studied also by light microscopy and transmission electron microscopy.
Keywords: Lung/Bronchoalveolar lavage/Antioxidant status/Stone wool/Glass fibres